PENGEMBANGAN E-MODUL KASUS KESULITAN PEMBELAJARAN TERINTEGRASI AL-QUR’AN PADA PESERTA DIDIK - Siti Rohani; Marzuki Noor; Hadi Pranoto (Counseling Milenial (CM), 2024)
The development of the E-Module on cases of learning difficulties integrated with the Koran is one of the appropriate counseling service media provided to students in schools. The research and development objectives that are expected in this study are to produce guidance and counseling service products in the form of E-Modules as a media solution for counseling services. The type of research is Research and Development, namely development research that uses quantitative data and qualitative data. This development research was conducted using the ASSURE development model. The research carried out resulted in the E-Modul product that the researcher developed managed to get results in the "Very Eligible" category. Thus, it can be concluded that the development of the E-Module on cases of learning difficulties integrated with the Koran is very effective for guidance and counseling teachers in overcoming problems that occur in schools. The developed E-Module is useful for students such as providing attractiveness to students in guidance and counseling services and solving learning difficulties that occur in students.